Pollution externalities in a Schumpeterian growth model - Simon Koesler (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2010)
This paper extends a standard Schumpeterian growth model to include an environmental dimension. Thereby, it explicitly links the pollution intensity of economic activity to technological progress. In a second step, it investigates the effect of pollution on economic growth under the assumption that pollution intensities are related to technological progress. Several conclusions emerge from the model. In equilibrium, the economy follows a balanced growth path. The effect of pollution on the economic growth rate vitally depends on the households' degree of pollution aversion and on the link between pollution intensity and the technology level. The decentralized solution does not meet the social optimum, though the social optimum can be implemented through the introduction of subsidies and pollution permits. Expectedly, the introduction of a pollution threshold stalls growth if pollution is not decoupled from economic growth and the possibility of pollution abatement allows the economy to grow at a higher rate.
Keywords: O41; Q51; Q55; Q56; 330; economic growth; endogenous pollution intensity; Schumpeter; Umweltbelastung; Neue Wachstumstheorie; Technischer Fortschritt; Umweltökonomik; Theorie